A New CBT Model of Panic Attack Treatment in Comorbid Heart Diseases (PATCHD): How to Calm an Anxious Heart and Mind. Issue 3 (August 2017) - Tully, Phillip J.; Sardinha, Aline; Nardi, Antonio E.
Abstract: Treating anxiety comorbid with heart disease is challenging due to (a) diagnostic overlap between anxiety and heart disease, (b) the high risk associated with ignoring chest pain symptoms and delaying seeking medical attention, (c) that cognitive-behavioral therapy based on catastrophic misinterpretation of bodily symptoms requires adaption to incorporate the element of risk, and (d) that certain interoceptive symptom induction experiments may be harmful and are therefore fraught with liability. We describe Panic Attack Treatment in Comorbid Heart Diseases (PATCHD) that is based on enhancing coping skills, performing safe interoceptive exposures and supervised exercise, and countering avoidance to reduce panic attack frequency. Pre- and posttreatment data from 18 patients shows a significant reduction in cardiovascular hospital admissions and length of stay, panic attacks, general anxiety, and depression (all p < .05). Because of the complex nature of panic disorder comorbid with heart disease, health professionals should familiarize themselves with several necessary CBT adaptions. Highlights: Panic disorder CBT requires substantial modification for persons with heart diseases There is risk associated with ignoring episodic chest pain symptoms and delaying medical attention We report a Panic Attack Treatment in Comorbid Heart Diseases (PATCHD) Some interoceptive symptom induction experiments may be harmful CBT practitioners should familiarize themselves with PATCHD if treating heart disease patients.